2019
DOI: 10.1016/j.actbio.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

New silyl-functionalized BisGMA provides autonomous strengthening without leaching for dental adhesives

Abstract: Resin-based composite has overtaken dental amalgam as the most popular material for direct restorative dentistry. In spite of this popularity the clinical lifetime of composite restorations is threatened by recurrent decay. Degradation of the adhesive leads to gaps at the composite/tooth interface—bacteria, bacterial by-products and fluids infiltrate the gaps leading to recurrent decay and composite restoration failure. The durability of resin-dentin bonds is a major problem. We address this problem by synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 75 publications
0
18
1
Order By: Relevance
“…We reported that the self-strengthening reaction is accelerated not only by heating but also by water [ 8 , 9 , 11 ]. The rubbery moduli and T g for the treated E1 increased significantly after one day of aqueous aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that the self-strengthening reaction is accelerated not only by heating but also by water [ 8 , 9 , 11 ]. The rubbery moduli and T g for the treated E1 increased significantly after one day of aqueous aging.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown improved properties for dental adhesives that achieve autonomous strengthening [ 8 , 9 , 11 , 12 ], little is known about the effect of this reaction on the cyclic-loading response during the early stages of network structure development. Within the clinical environment, the d/a interface will be subjected to cyclic stress and these stresses challenge both the durability of the adhesive and the integrity of the d/a interface [ 31 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mechanical properties following aqueous aging and the significant decrease in leached HEMA reflect a resistance to hydrolysis in the silyl‐BisGMA adhesive formulations. The introduction of silyl‐BisGMA in the adhesive formulation led to higher crosslinked networks as compared to BisGMA/HEMA formulations . The higher crosslinked networks are envisioned as an important component of a multi‐factorial approach to durable adhesives.…”
Section: Strategies To Increase the Durability Of Adhesivesmentioning
confidence: 99%
“…In the MPS‐containing formulations, the rate of hydrolysis of the trialkoxysilyl group is relatively slow as compared to the free radical polymerization of the CC bonds in the methacrylate monomers. The autonomic sol–gel reaction provided a slow and continued reaction, which can gradually generate the SiOSi bond and resist hydrolytic degradation …”
Section: Strategies To Increase the Durability Of Adhesivesmentioning
confidence: 99%
“…Adhesive composite restorations are threatened by secondary caries, the degradation of the adhesive layer present at the interface between the tooth and by the various defective restorationmaterials, which will then be infested by fluids, bacteria and secondary bacterial products, leading ultimately to the failure of the composite filling. Therefore the durability over time of the connections between dentin and adhesives become an issue [3].…”
mentioning
confidence: 99%